Continuation of Shishi Matsuri Festival in Murashima village, Japan - Kahraman, Cahit (Border Crossing, 2016)
Shishi Matsuri or the Lion Festival is very popular and is often observed in different parts of Japan. Known also as Shishimai or Lion Dance performance, it is a religious festival and an art performance. The fieldwork for this study was carried out in Murashima village, Sugeta town, Ehime prefecture, Japan. The festival is held annually in November and involves everyone in the village. The performers are the local villagers themselves. Although Shishi Matsuri reinforces the sense of belonging, it also creates a sense of collectivity and unity as everyone joins in. Continuation of a tradition of this kind is bound with a number of difficulties and challenges. Financial issues, decreasing young population and natural disasters are but a few such matters faced every year. This study aims to understand the reasons and motivations that make it possible for the community members to carry on with the tradition of the festival despite challenges and difficulties.